Moderate population structure in drosophila sturtevanti from the south american atlantic forest biome - Trava, Bruna Memari [UNESP]; Mateus, Rogério Pincela; Machado, Luciana Paes de Barros; Madi-Ravazzi, Lilian [UNESP] (My University, 2021)
Drosophila sturtevanti is a widely distributed Neotropical species. In South America, it is abundant and adapted to different phytophysiognomies of the Atlantic Forest biome. Reproductive, chromosomal and enzymatic studies have indicated the existence of a differentiation among D. sturtevanti populations. In this work, the level of genetic diversity and the population genetic structure were analyzed using four population groupings. One hundred and twenty-six D. sturtevanti males collected from nine forest fragments were analyzed for 11 species-specific microsatellite loci. A total of 109 alleles, ranging from 2 to 16 alleles per locus, were detected. The highest mean observed heterozygosity-HO was estimated in samples from the largest collection areas, and the lowest HO was from a population where fire events are common. A low molecular variation, around 3% among populations and negative among groups, an absence of genetic and geographic correlations and a moderate genetic differentiation-FST = 0.0663-indicated that D. sturtevanti is not strongly structured. Besides no overall genetic and geographic distance correlation, the pair of closest geographically populations Matão and Nova Granada showed the lower differentiation through FST, DC and a Neighbor Joining tree. Ribeirão da Ilha-RDI, an isolated insular population, was the most differentiated according to FST, DC and a cluster-based Bayesian analysis. The isolation of RDI that resulted in significant divergence could be ancient, because of sea level regressions/ transgressions, or more recently via founder effect/genetic drift by anthropic action carrying D. sturtevanti hosts from continent to island. This work is important for understanding the genetic variability distribution of a Neotropical forest-dwelling Drosophila species using for the first time, a wide population distribution approach.
Keywords: Forest fragmentation; Genetic diversity; Population differentiation; Saltans group; Simple sequence repeats